Death From Stroke in End-Stage Kidney Disease: A Population-Based Study Using Data Linkage. Issue 2 (February 2019) - De La Mata, Nicole L.; Masson, Philip; Al-Shahi Salman, Rustam; Kelly, Patrick J.; Webster, Angela C.
Abstract : Background and Purpose—: People with end-stage kidney disease (ESKD) are at greater risk of stroke. We aimed to compare stroke mortality between the ESKD population and the general population. Methods—: We included all patients with incident ESKD in Australia, 1980 to 2013, and New Zealand, 1988 to 2012. The primary cause of death was ascertained using data linkage with national death registers. We produced standardized mortality ratios for stroke deaths, by age, sex, and calendar year. Results—: We included 60 823 patients with ESKD, where 941 stroke deaths occurred during 381 874 person-years. Patients with ESKD had >3× the stroke deaths compared with the general population (standardized mortality ratio, 3.4; 95% CI, 3.2–3.6), markedly higher in younger people and women. The greatest excess was in intracerebral hemorrhages (standardized mortality ratio, 5.2; 95% CI, 4.5–5.9). Excess stroke deaths in patients with ESKD decreased over time, although were still double in 2013 (2013 standardized mortality ratio, 2.1; 95% CI, 1.5–2.9). Conclusions—: People with ESKD experience much greater stroke mortality with the greatest difference for women and younger people. However, mortality has improved over time. Abstract : Supplemental Digital Content is available in the text.